ACID MINE DRAINAGE MANAGEMENT USING CATCHMENT AREA APPROACH CASE STUDY : UKUD RIVER, SITE LATI - SONNY ABFERTIAWAN (NIM : 22108318), MUHAMMAD
This study aims to assess and develop methods catchment area approach to the management of acid mine water in Ukud River that flows coal mining areas, Berau used as a case study. Actual Ukud River catchment area covers 10 Subcatchment with total area 1738.67 Ha. Disposal area covers 48.6% of the total area and 51.4% of land is still a original area. 48.6% of the disposal area is only 48% that has been conducted revegetation. Overburden characteristics in Ukud River catchment has the potential to form acids that appear in the NAG test of 60 sample points. A10 is a downstream subcatchment of the River Ukud. The total discharge of the catchment will pass through this A10 at 13,379.24 liters/second. Which is the Area Compliance Point (CP) from the River Ukud has pH 4.23. Sulfate concentration is high on the value of 92.83 mg/liter. Ion the Fe2+ and Fe3+ are in the value of 9.05 mg/liter and 4.62 mg/liter. While the metals Al and Mn measured in the value of 9.67 mg/liter and 4.07 mg/liter TDS value of 735.55 mg/liter which describes the content of dissolved metal ions. There are three subcatchment which has a large influence pollutant affecting the quality streams ie A1, A8, and A9. Two approaches namely the first approach (SO4 dilution factor, precipitation factor, and redox changes factor) and the second approach (the dilution of H+ concentration approaches) are used to show the pattern of changes in pH value at the point J5 as CP. Diluted concentrations of H+ is used to model the conditions of pH changes at the point CP. Changes in the quality of the three influential catchment provides an increase in pH up to 5.01.